2005
DOI: 10.1016/j.visres.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive modulation of color salience contingent upon global form coding and task relevance

Abstract: Extensive research on local color aftereffects has revealed perceptual consequences of opponent color coding in the retina and the LGN, and of orientation-and/or spatial-frequency-contingent color coding in early cortical visual areas (e.g., V1 and V2). Here, we report a color aftereffect that depends crucially on global-form-contingent color processing. Brief viewing of colored items (passively viewed, ignored, or attended) reduced the salience of the previewed color in a subsequent task of color-based visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 103 publications
8
56
5
1
Order By: Relevance
“…In other words, selective attention is required for negative priming to take place. In contrast, previous studies Ariga, Lleras, & Kawahara, 2004;Goolsby et al, 2005) have shown that selective attention is not required for the DPE to occur. For example, Ariga et al showed that a DPE could be observed even when the target-present display contained only one item.…”
Section: The Distractor-previewing Effectcontrasting
confidence: 69%
See 3 more Smart Citations
“…In other words, selective attention is required for negative priming to take place. In contrast, previous studies Ariga, Lleras, & Kawahara, 2004;Goolsby et al, 2005) have shown that selective attention is not required for the DPE to occur. For example, Ariga et al showed that a DPE could be observed even when the target-present display contained only one item.…”
Section: The Distractor-previewing Effectcontrasting
confidence: 69%
“…Similarly, Goolsby et al (2005), using the same color stimuli used in the present study, also showed a dissociation between these two effects by showing that priming of pop-out was due to attention-based color segmentation (which occurs when there is no pop-out item on the preceding trial but the attended/ignored color segmentation is repeated between trials), whereas the DPE was due to processing of uniformly colored items. Thus, the DPE can take place in the absence of priming of pop-out.…”
Section: The Distractor-previewing Effectsupporting
confidence: 68%
See 2 more Smart Citations
“…The DPE reflects a tendency to be much slower and less accurate to select a target on a target-present trial (e.g., a red oddball item) when its target-defining characteristic (red) was associated with the absence of targets in the preceding target-absent trial (i.e., when all items in the preceding trial were red). See Goolsby, Grabowecky, and Suzuki (2005) and Lleras, Kawahara, Wan, and Ariga (2008). The effect is observed in temporal tasks, as well (Lleras, Kawahara, & Levinthal, 2009), and transfers across spatial and temporal tasks (Levinthal & Lleras, 2008).…”
mentioning
confidence: 99%